2012
DOI: 10.1093/jac/dks209
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin versus clarithromycin in a 10 day triple therapy regimen for first-line Helicobacter pylori eradication: a single-blind randomized clinical trial

Abstract: Levofloxacin-based treatment for H. pylori infection did not improve upon the eradication rate of the standard clarithromycin-based triple therapy in this study. This may reflect the progressive increase in in vitro resistance rates to levofloxacin observed in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Similar rates are reported for moxifloxacin resistance [16,17,18,19,20]. Quinolon resistance increases with age and duration of use.…”
Section: Discussionsupporting
confidence: 79%
“…Similar rates are reported for moxifloxacin resistance [16,17,18,19,20]. Quinolon resistance increases with age and duration of use.…”
Section: Discussionsupporting
confidence: 79%
“…Boyanova et al (41) reported an 8% metronidazole/clarithromycin resistance rate in H. pylori strains. In a study performed in 2012 in Spain, the authors reported an 18.1% multidrug resistance rate, with the metronidazole/quinolone resistant phenotype as the predominant phenotype (3) . In the present study, multiple resistance was observed in 52.7% (19/36) of the 36 clarithromycin-resistant strains.…”
Section: Financial Supportmentioning
confidence: 99%
“…Helicobacter pylori is thought to be involved in the pathogenesis of gastritis, peptic ulcer disease, gastric cancer, mucosa-associated lymphoid tissue lymphoma and various extra-gastrointestinal manifestations (1) (2) (3) . Unfortunately, emerging bacterial resistance causes treatment problems, leading to a search for new treatment regimens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2012 Maastricht consensus guideline recommends the levofloxacin-PPI containing regimen for patients who have failed standard first-line treatment [2]. Many studies have examined levofloxacin-PPI as a first-line therapy for eradication of H pylori infection [8][10]. However, the eradication rates achieved with first-line levofloxacin-based treatments are not uniform.…”
Section: Introductionmentioning
confidence: 99%